Novel Splicing Mutation in B3GAT3 Associated with Short Stature, GH Deficiency, Hypoglycaemia, Developmental Delay, and Multiple Congenital Anomalies. (28th November 2017) - Bloor, Samuel; Giri, Dinesh; Didi, Mohammed; Senniappan, Senthil
Abstract : B3GAT3, encoding β -1, 3-glucuronyltransferase 3, has an important role in proteoglycan biosynthesis. Homozygous B3GAT3 mutations have been associated with short stature, skeletal deformities, and congenital heart defects. We describe for the first time a novel heterozygous splice site mutation in B3GAT3 contributing to severe short stature, growth hormone (GH) deficiency, recurrent ketotic hypoglycaemia, facial dysmorphism, and congenital heart defects. A female infant, born at 34 weeks' gestation to nonconsanguineous Caucasian parents with a birth weight of 1.9 kg, was noted to have cloacal abnormality, ventricular septal defect, pulmonary stenosis, and congenital sensorineural deafness. At 4 years of age, she was diagnosed with GH deficiency due to her short stature (height < 2.5 SD). MRI of the pituitary gland revealed a small anterior pituitary. She has multiple dysmorphic features: anteverted nares, small upturned nose, hypertelorism, slight frontal bossing, short proximal bones, hypermobile joints, and downslanting palpebral fissures. Whole exome sequencing (WES) was performed on the genomic DNA from the patient and biological mother. A heterozygous mutation in B3GAT3 (c.888+262T>G) in the invariant "GT" splice donor site was identified. This variant is considered to be pathogenic as it decreases the splicing efficiency in the mRNA.